La enseñanza de la química desde la perspectiva de la Química Verde - González-García, Pía José; Pérez-Mendez, Claudio; Figueroa-Duarte, Sebastián (Revista Científica, 2016)
Green Chemistry (GC), as a research area, understood as the development of methodologies to modify products or processes in order to reduce or eliminate the risks posed to the environment and human health. Thus it is allowing research project lines in building knowledge and didactic approaches of the sciences, and to be considered as part of the ministerial programs. The objective of this study was to know and understand the significance given by teachers in the area to GC as a perspective for education. From the speeches issued by teachers participating in the study, four categories, was built. GC as: context for teaching chemistry, through significant learning chemistry appropriation, motivating environmental awareness and reflection of the institution and its relationship with teachers.